Assessment of variable separation for finite element modeling of free edge effect for composite plates. (May 2015) - Vidal, P.; Gallimard, L.; Polit, O.
Abstract: This paper deals with the assessment of an approach based on the separation of variables for the modeling of the free edge effect in laminated composite plates. This is of major importance for damage of composite structures. The displacement field is approximated as a sum of separated functions of the in-plane coordinates x, y and the transverse coordinate z . This choice yields to an iterative process that consists of solving a 2D and 1D problem successively at each iteration. In the thickness direction, a fourth-order expansion in each layer is considered. For the in-plane description, classical finite element method is used. Numerical examples involving several representative laminates subjected to uniaxial tension are addressed to show the capability of the present LW method to capture the steep transverse stress gradients occurring in the vicinity of free edges. It is shown that it can provide quasi-3D results less costly than 3D FEM computations.